The existence of independent non-executive directors towards public listed companies' performance in Malaysia / Flicia Rimin - Rimin, Flicia (2014)
A growing concern over the importance of Corporate Governance began to attain it is attention as investors awakened by the tragedy that fell during the Financial Crisis 1997. The effects of this crisis have infected many Asian countries and in particular the Malaysian economies due to a major reason for lacking a substantial corporate governance. In relation to this, the Malaysian government has conducted extensive reforms in regulatory, legal, and reporting framework relating to shareholders rights, management oversights and other monitoring mechanisms, followed with the amendments to the Malaysian stock exchange's Listing Requirements and the setting up of the high-level finance committee of corporate governance. The Ministry of Finance have "therefore" established the first Code of Corporate Governance in the year 2000, followed by a revised edition of2007 which required at least a one third of the board membership are independent directors. This is to ensure a proper conduct by the board of directors towards the company's operation and their accountability to the shareholders. However, despite the positive reasons of their existence, there are discrepancies in findings and arguments among the researchers relating to their effectiveness to influence a company's performance. Thus, the findings of this study indicate the elements of corporate governance such as the number of independent non-executive directors and directors' remuneration have no significant relationship